DFT studies on molecular and electronic structures of cationic carbene complexes [L2(η5-C5H5)Fe=CR5]+ (L = CO, PH3, dhpe, PPh3; R = H, F, CH3) - Hyla-Kryspin, Isabella (Array, 2009)
Summary: For the title complexes we discuss the results of DFT calculations for (i) the molecular and electronic structures, (ii) the rotational barriers of the carbenes around the Fe=Ccarb bond (ΔErot), and (iii) the binding energies of the carbenes (De). Where available, the calculated properties of the Fe=Ccarb bonds are compared with previous theoretical and experimental data of some prototypical carbene complexes classified as Fischer- or Schrock-type compounds. It is shown that the rotational barriers of the carbenes, the Fe−Ccarb bond distances and bond strengths are sensitive to the carbene substituents and to the ligands L attached to iron. For complexes with given L the values of ΔErot diminish in the order: CH2 > CF2 > CMe2 and an inverse ordering is obtained for the decrease of the Fe=Ccarb bond distance. The ΔErot of dimethylcarbene are close to those of Fischer-type compounds, while ΔErot of methylidene approach values typical for Schrock-type carbenes. The replacement of the CO ligand by poorer π-acceptor ligand increases the values of ΔErot in the order: CO < PH3 < dhpe < PPh3 and diminishes the Fe−Ccarb bond distance in the same order. The binding energies (De) of the carbenes are larger than the first dissociation energy of CO from the pentacarbonyliron complex. For complexes with given L, except one, the De values decrease in the order: CH2 > CMe2 > CF2. The properties of the investigated compounds are traced back to the character of the Fe → Ccarb π-backbonding interactions and their competitions with the Fe → L and R → Ccarb π- interactions. It is also shown that the PH3 ligand can only be considered with caution as a good model for the PPh3 ligand in computational studies